Self-report measures of medication adherence behavior: recommendations on optimal use. Issue 4 (9th July 2015) - Stirratt, Michael J.; Dunbar-Jacob, Jacqueline; Crane, Heidi M.; Simoni, Jane M.; Czajkowski, Susan; Hilliard, Marisa E.; Aikens, James E.; Hunter, Christine M.; Velligan, Dawn I.; Huntley, Kristen; Ogedegbe, Gbenga; Rand, Cynthia S.; et al.
Abstract: Medication adherence plays an important role in optimizing the outcomes of many treatment and preventive regimens in chronic illness. Self-report is the most common method for assessing adherence behavior in research and clinical care, but there are questions about its validity and precision. The NIH Adherence Network assembled a panel of adherence research experts working across various chronic illnesses to review self-report medication adherence measures and research on their validity. Self-report medication adherence measures vary substantially in their question phrasing, recall periods, and response items. Self-reports tend to overestimate adherence behavior compared with other assessment methods and generally have high specificity but low sensitivity. Most evidence indicates that self-report adherence measures show moderate correspondence to other adherence measures and can significantly predict clinical outcomes. The quality of self-report adherence measures may be enhanced through efforts to use validated scales, assess the proper construct, improve estimation, facilitate recall, reduce social desirability bias, and employ technologic delivery. Self-report medication adherence measures can provide actionable information despite their limitations. They are preferred when speed, efficiency, and low-cost measures are required, as is often the case in clinical care.